The Gynecologic Laparoscopic Surgery: Experience of Center of Fertility and Reproductive Medicine at St. Paul’s Hospital Millennium Medical College - Kasa, Ayallew; Abdella, Mustefa (Ethiopian Journal of Reproductive Health, 2022)
Background: Recent data suggests that up to 80% of gynecologic surgeries can be accomplished laparoscopically. However, laparoscopy does not come without risks – specifically risks of injury to the bowel, urinary tract, and vasculature. This study assesses the indications for, as well as the complications and outcomes of laparoscopic surgery at the Center of Fertility and Reproductive Medicine at St Paul’s Hospital Millennium Medical College. Methods and Materials: This is a cross sectional retrospective study using data abstracted from medical records between April 2019 to September 2020. We included all gynecologic laparoscopies done during this date range. The data was collected with Open Data Kit (ODK) software and then transferred to Microsoft Excel for analysis. We set statistical significance at P <0.05. Results: There were 135 gynecologic surgeries performed, with a mean patient age of 32.4 years. About two-thirds of them presented with primary infertility, and 30% had a previous laparotomy or laparoscopy. Twenty percent had previously been diagnosed with tuberculosis. The main indication for laparoscopy was hydrosalpinx which accounted for 51.1% of surgeries. For patients who underwent surgery for a diagnosis of hydrosalpinx, the majority (54%) underwent bilateral salpingectomy. Our complication rate was 3.7% and rate of conversion to laparotomy was 5.2%. Conclusion: Our complication rate was higher than previously published laparoscopic complication rates from Asia and Europe. The majority of our complications were bladder and bowel injuries. Complications were managed predominately by conversion to laparotomy. Keywords: gynecology, laparoscopy, complications, Saint Paul’s Hospital Millennium Medical College.